Find expert answers and community insights on IDNLearn.com. Find the answers you need quickly and accurately with help from our knowledgeable and dedicated community members.

Find the derivative of the function.

[tex]\[
\begin{array}{l}
y = 4 \sqrt{x} + 5 x^{\frac{1}{5}} \\
\frac{d y}{d x} = \square
\end{array}
\][/tex]


Sagot :

Sure, let's find the derivative of the given function step-by-step.

We start with the function:
[tex]\[ y = 4 \sqrt{x} + 5 x^{\frac{1}{5}} \][/tex]

To differentiate this function, we will apply the power rule for derivatives, which states that for any term [tex]\( x^n \)[/tex], the derivative is [tex]\( n x^{n-1} \)[/tex].

First, let's rewrite the square root of [tex]\( x \)[/tex] using exponents:
[tex]\[ \sqrt{x} = x^{\frac{1}{2}} \][/tex]

Now the function becomes:
[tex]\[ y = 4 x^{\frac{1}{2}} + 5 x^{\frac{1}{5}} \][/tex]

Next, we differentiate each term individually.

1. For the first term, [tex]\( 4 x^{\frac{1}{2}} \)[/tex]:

[tex]\[ \frac{d}{dx} \left( 4 x^{\frac{1}{2}} \right) = 4 \cdot \frac{1}{2} x^{\frac{1}{2} - 1} = 2 x^{-\frac{1}{2}} \][/tex]

2. For the second term, [tex]\( 5 x^{\frac{1}{5}} \)[/tex]:

[tex]\[ \frac{d}{dx} \left( 5 x^{\frac{1}{5}} \right) = 5 \cdot \frac{1}{5} x^{\frac{1}{5} - 1} = x^{-\frac{4}{5}} \][/tex]

So the derivative of [tex]\( y \)[/tex] with respect to [tex]\( x \)[/tex] is:
[tex]\[ \frac{d y}{d x} = 2 x^{-\frac{1}{2}} + x^{-\frac{4}{5}} \][/tex]

Let's rewrite those terms to make them easier to understand. Remembering that:

[tex]\[ x^{-\frac{1}{2}} = \frac{1}{x^{\frac{1}{2}}} = \frac{1}{\sqrt{x}} \][/tex]

[tex]\[ x^{-\frac{4}{5}} = \frac{1}{x^{\frac{4}{5}}} \][/tex]

And since [tex]\(\frac{1}{x^{\frac{4}{5}}} = \frac{1}{x^{0.8}} \)[/tex], then:

[tex]\[ \frac{d y}{d x} = \frac{2}{\sqrt{x}} + \frac{1}{x^{0.8}} \][/tex]

Thus, the final result is:
[tex]\[ \boxed{\frac{d y}{d x} = \frac{1}{x^{0.8}} + \frac{2}{\sqrt{x}}} \][/tex]